Robert Morrison and the Protestant plan for China - Daily, Christopher A. (Royal Asiatic Society books., 2013)
Robert Morrison, sent alone to his East Asian post by the London Missionary Society in 1807, was the first Protestant missionary to operate in China. During some 27 years in China, Macau and Malacca, he worked as a translator, founded an academy for converts and missionaries, translated the New Testament into Chinese, and compiled the first Chinese-English dictionary. In this process, he was building the foundation of Chinese Protestant Christianity. Chinese Protestant Christianity has become one of the largest Christian churches in the world and the fastest growing religion in China. This book demonstrates the many ways in which Morrison's influential mission must be seen within the historical and ideological contexts of British evangelism. The result is a new interpretation of the beginnings of Protestant Christianity in China.